Molecular Dynamics Simulation of the Coalescence and Melting Process of Cu and Ag Nanoparticles - Hui Guo; LinFu Zhang; Qiang Zhu; ChuanJie Wang; Gang Chen; Peng Zhang (Advances in Condensed Matter Physics)
The coalescence and melting process of different sizes and arrangements of Ag and Cu nanoparticles is studied through the molecular dynamics (MD) method. The results show that the twin boundary or stacking fault formation and atomic diffusion of the nanoparticles play an important role in the different stages of the heating process. At the beginning of the simulation, Cu and Ag nanoparticles will contact to each other in a very short time. As the temperature goes up, Cu and Ag nanoparticles may generate stacking fault or twin boundary to stabilize the interface structure. When the temperature reaches a critical value, the atoms gain a strong ability to diffuse and eventually melt into one liquid sphere. The coalescence point and melting temperature increase as cluster diameter increases. Moreover, the arrangement of Cu and Ag nanoparticles has a certain effect on the stability of the initial joint interface, which will affect subsequent coalescence and melting behavior.